Metabolomic profiling of saliva from cystic fibrosis patients - M. Caterino; M. Costanzo; A. Castaldo; P. Iacotucci; V. Carnovale; M. Ruoppolo; M. Gelzo; G. Castaldo (Scientific Reports)
Abstract The development of targeted therapies that correct the effect of mutations in patients with cystic fibrosis (CF) and the relevant heterogeneity of the clinical expression of the disease require biomarkers correlated to the severity of the disease useful for monitoring the therapeutic effects. We applied a targeted metabolomic approach by LC-MS/MS on saliva samples from 70 adult CF patients and 63 age/sex-matched controls to investigate alterations in metabolic pathways related to pancreatic insufficiency (PI), Pseudomonas aeruginosa (PA) colonization, CF liver disease (CFLD), and CF related diabetes (CFRD). Sixty salivary metabolites were differentially expressed, with 11 being less abundant and 49 more abundant in CF patients. Among these, the most relevant alterations involved salivary ADMA, N-acetylornithine, methionine and methionine sulfoxide levels. Furthermore, methionine was significantly lower in CF patients with PI and salivary histamine levels were significantly lower in patients colonized by PA. Moreover, ADMA as well as N-acetylornithine and methionine were significantly lower in CF patients with CFRD than in patients without CFRD. Finally, the levels of DOPA resulted significantly lower in saliva from patients with liver disease. Our study revealed an imbalance in arginine methylation and tryptophan pathway related to CFRD and PI as well as alterations in dopaminergic pathway and Krebs cycle related to CFLD. This study also highlights different salivary metabolites as new potential biomarkers in a non-invasive sample that could represent a useful tool for the stratification and management of CF patients.